Fracture strength of incisor crowns after intracoronal bleaching with sodium percarbonate - Kuga, Milton Carlos [UNESP]; dos Santos Nunes Reis, Jose Mauricio [UNESP]; Fabricio, Semiramis [UNESP]; Bonetti-Filho, Idomeo [UNESP]; Campos, Edson Alves de [UNESP]; Faria, Gisele [UNESP] (Wiley-Blackwell, 2012)
Objectives: To compare the fracture resistance of bovine teeth after intracoronal bleaching with sodium percarbonate (SPC) or sodium perborate (SP) mixed with water or 20% hydrogen peroxide (HP). Materials and methods: Fifty extracted bovine teeth were divided into four experimental groups (G1G4) and one control (n = 10) after endodontic treatment. Following root canal obturation, a glass ionomer barrier was placed at the cementoenamel junction. After that, the pulp chambers were filled with: G1 SP with water; G2 SP with 20% HP; G3 SPC with water; and G4 SPC with 20% HP. No bleaching agent was used in the control group. Coronal access cavities were sealed with glass ionomer and specimens were immersed in artificial saliva. The bleaching agents were replaced after 7 days, and teeth were kept in artificial saliva for an additional 7 days, after which the pastes were removed and the coronal access cavities were restored with glass ionomer. Crowns were subjected to compressive load at a cross head speed of 0.5 mm min-1 applied at 135 degrees to the long axis of the root by an EMIC DL2000 testing machine, until coronal fracture. Data were statistically analysed by anova and Tukey test. Results: No differences in fracture resistance were observed between the experimental groups (P > 0.05). However, all experimental groups presented lower fracture resistance than the control group (P < 0.05). Conclusion: SPC and SP led to equal reduction on fracture resistance of dental crowns, regardless of being mixed with water or 20% HP.